Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s11258-006-9183-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prescribed burning on plant available nutrients in dry heathland ecosystems

Abstract: Heathland management is an important tool with which to modify ecosystem impacts caused by atmospheric nutrient deposition. Since changes in nutrient availability as a result of management measures affect the outcomes of heathland succession and species competition, studies on this issue are important from both a nature conservation and management point of view. This study reports the effects of prescribed burning on nutrient availability in dry heathland soils and the nutrient content of the two competing hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The high levels of atmospheric nitrogen deposition require considerable habitat management efforts. Management measures such as grazing, prescribed burning, or sod-cutting, may partly compensate for atmospheric N loads, but are expensive, particularly for large habitat patches Mohamed et al 2006;Müller and Schaltegger 2004;Niemeyer et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The high levels of atmospheric nitrogen deposition require considerable habitat management efforts. Management measures such as grazing, prescribed burning, or sod-cutting, may partly compensate for atmospheric N loads, but are expensive, particularly for large habitat patches Mohamed et al 2006;Müller and Schaltegger 2004;Niemeyer et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although one would expect the deposition of basic ash to have raised pH values in the subplots subjected to burning (Forgeard 1990), increased nitrification rates and, thus, liberation of protons may in fact have compensated for a pH increase (Brady and Weil 2002;Mohamed et al 2006). In our experiment, soil pH proved to be an inappropriate indicator of internal turnover processes.…”
Section: Soil Ph H 2 Omentioning
confidence: 65%
“…The significant increase in Ca and Mg leaching in the burned subplots can be attributed to the deposition of ash containing high amounts of Ca and Mg (Niemeyer et al 2005). Since plant uptake was limited and amounts of seepage water increased after burning, post-management leaching of these cations significantly increased (Mohamed et al 2006). The high leaching rates for Ca found for the choppering controls were probably due to slightly higher loam contents at these sites.…”
Section: Soil Ph H 2 Omentioning
confidence: 96%
“…In addition to its successful use at Abernethy Forest for the promotion of Scots pine establishment, the management of heather moorland vegetation by prescribed burning is practiced widely in the UK (Yallop et al 2006). Such burning can influence nutrient availability (Niemeyer et al 2005;Mohamed et al 2007) and has been shown to alter patterns of fungal fruiting at Abernethy Forest, with mycorrhizal taxa observed to fruit more abundantly in the year following burning (Amphlett et al 2006). Until now, however, analysis of the effects of burning on below-ground communities of fungi and microbial activities has been lacking.…”
Section: Discussionmentioning
confidence: 99%